ER stress increases store-operated Ca(2+) entry (SOCE) and augments basal insulin secretion in pancreatic beta cells - Zhang, Irina X. (J Biol Chem, 2020)
Type 2 diabetes mellitus (T2DM) is characterized by impaired glucose-stimulated insulin secretion and increased peripheral insulin resistance. Unremitting endoplasmic reticulum (ER) stress can lead to beta-cell apoptosis and has been linked to type 2 diabetes. Although many studies have attempted to link ER stress and T2DM, the specific effects of ER stress on beta-cell function remain incompletely understood. To determine the interrelationship between ER stress and beta-cell function, here we treated insulin-secreting INS-1(832/13) cells or isolated mouse islets with the ER stress–inducer tunicamycin (TM). TM induced ER stress as expected, as evidenced by activation of the unfolded protein response. Beta cells treated with TM also exhibited concomitant alterations in their electrical activity and cytosolic free Ca(2+) oscillations. As ER stress is known to reduce ER Ca(2+) levels, we tested the hypothesis that the observed increase in Ca(2+) oscillations occurred because of reduced ER Ca(2+) levels and, in turn, increased store-operated Ca(2+) entry. TM-induced cytosolic Ca(2+) and membrane electrical oscillations were acutely inhibited by YM58483, which blocks store-operated Ca(2+) channels. Significantly, TM-treated cells secreted increased insulin under conditions normally associated with only minimal release, e.g. 5 mm glucose, and YM58483 blocked this secretion. Taken together, these results support a critical role for ER Ca(2+) depletion–activated Ca(2+) current in mediating Ca(2+)-induced insulin secretion in response to ER stress.